2014
DOI: 10.2475/07.2014.02
|View full text |Cite
|
Sign up to set email alerts
|

The Jabal Akhdar dome in the Oman Mountains: Evolution of a dynamic fracture system

Abstract: ABSTRACT. The Mesozoic succession of the Jabal Akhdar dome in the Oman

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 81 publications
4
53
0
Order By: Relevance
“…Virgo (2015) summarizes the deformation events into seven phases (I-VII) with possible relation to the geodynamic context. He related his findings with Hilgers (2006), Holland et al (2009a) and Gomez-Rivas et al (2014) and found these to be in general agreement. The phases are as follows: …”
Section: Geological Setting and Study Areasupporting
confidence: 71%
See 4 more Smart Citations
“…Virgo (2015) summarizes the deformation events into seven phases (I-VII) with possible relation to the geodynamic context. He related his findings with Hilgers (2006), Holland et al (2009a) and Gomez-Rivas et al (2014) and found these to be in general agreement. The phases are as follows: …”
Section: Geological Setting and Study Areasupporting
confidence: 71%
“…Most importantly for this study, SW directed obduction of the volcanic-sedimentary Hawasina nappes and Semail ophiolite nappe started at the end of Cretaceous, during the Cenomanian (Breton et al, 2004;Glennie et al, 1974;Searle, 2007). After nappe emplacement the whole region underwent several episodes of extension and transpression that were followed by uplift, doming and erosion of the Jebel Akhdar Anticline (Al-Wardi and Butler, 2007;Breton et al, 2004;Filbrandt et al, 2006;Fournier et al, 2006;Gomez-Rivas et al, 2014;Hanna, 1990).…”
Section: Geological Setting and Study Areamentioning
confidence: 97%
See 3 more Smart Citations